Sensorimotor impairment and haptic support in microgravity - Weber, Bernhard; Riecke, Cornelia; Stulp, Freek (Experimental brain research, 2021)
Future space missions envisage human operators teleoperating robotic systems from orbital spacecraft. A potential risk for such missions is the observation that sensorimotor performance deteriorates during spaceflight. This article describes an experiment on sensorimotor performance in two-dimensional manual tracking during different stages of a space mission. We investigated whether there are optimal haptic settings of the human-machine interface for microgravity conditions. Two empirical studies using the same task paradigm with a force feedback joystick with different haptic settings (no haptics, four spring stiffnesses, two motion dampings, three masses) are presented in this paper. (1) A terrestrial control study ( N = 20 subjects) with five experimental sessions to explore potential learning effects and interactions with haptic settings. (2) A space experiment ( N = 3 cosmonauts) with a pre-mission, three mission sessions on board the ISS (2, 4, and 6 weeks in space), and a post-mission session. Results provide evidence that distorted proprioception significantly affects motion smoothness in the early phase of adaptation to microgravity, while the magnitude of this effect was moderated by cosmonauts’ sensorimotor capabilities. Moreover, this sensorimotor impairment can be compensated by providing subtle haptic cues. Specifically, low damping improved tracking smoothness for both motion directions (sagittal and transverse motion plane) and low stiffness improved performance in the transverse motion plane.